Gel electrolyte, lithium ion battery and preparation method thereof
By using gel electrolytes of specific compositions in lithium-ion batteries, the safety hazards of traditional liquid electrolytes and the problem of excessive gel polymer content in gel electrolytes are solved, and the high cycle performance and rate performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202510370233.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional liquid lithium-ion batteries have safety hazards such as liquid leakage and combustion, and the content of gel polymer in the gel electrolyte is too high, affecting the circulation and rate performance of lithium-ion batteries.
Using a gel electrolyte including a gel polymer, a lithium salt and an organic solvent, the gel polymer consists of a carbonate polymer monomer and a crosslinking agent having a plurality of C=C. The mass ratio of the polymer monomer to the crosslinking agent and the content of the gel polymer are limited within a specific range to form a multi-dimensional, porous structure polymer network.
It improves the circulation performance and rate performance of lithium-ion batteries, while reducing the cost of gel electrolytes, and solving the safety hazards of liquid electrolytes.
Smart Images

Figure CN119905654A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a gel electrolyte, a lithium ion battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, and good safety, and are widely used in various fields such as portable power storage, electronic equipment, and electric vehicles. At present, traditional commercial secondary batteries mainly use liquid organic electrolytes as lithium ion transmission media for energy storage and conversion. Liquid electrolytes are prone to leakage, internal short circuits, thermal abnormalities, malignant combustion or explosion, and other safety hazards.
[0003] Gel electrolytes use polymer networks to absorb liquid electrolytes, which can solve potential safety issues such as leakage and combustion of liquid electrolytes. They have always been a focus of industry and academia. However, the gel polymer content in gel electrolytes reported so far is generally high, which not only increases the cost, but also seriously affects the cycle performance and rate performance of lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide a gel electrolyte, a lithium ion battery and a preparation method thereof, so as to improve the cycle performance and rate performance of the lithium ion battery. The specific technical scheme is as follows:
[0005] The first aspect of the present application provides a gel electrolyte, which includes a gel polymer, a lithium salt and an organic solvent; the gel polymer includes monomer units from a polymerized monomer and a cross-linking agent, the polymerized monomer is selected from a carbonate compound, the carbonate compound is selected from at least one of a cyclic carbonate and a linear carbonate; the cyclic carbonate is selected from at least one of the compounds shown in Formula Ia; the linear carbonate is selected from at least one of the compounds shown in Formula Ib;
[0006] Among them, A is selected from , B is selected from C2-C8 alkenyl; R1 and R2 are each independently selected from C1-C4 alkyl or C2-C5 alkenyl, and contain at least one unsaturated bond, 1≤x≤2;
[0007] The cross-linking agent is selected from at least one of the compounds shown in Formula II;
[0008] Wherein, R3 to R6 are each independently selected from C1-C4 alkyl or , and contains at least two , 0≤n≤3;
[0009] Based on the mass of the gel electrolyte, the mass percentage w of the gel polymer is 1% to 20%;
[0010] The mass ratio m1 / m2 of the polymerizable monomer to the cross-linking agent is 0.1-4.
[0011] In one embodiment of the present application, w is 1.5% to 10%, and m1 / m2 is 0.5 to 2.
[0012] In one embodiment of the present application, B is selected from or ; R7 and R8 are each independently selected from a hydrogen atom, a C1-C4 alkyl group or a C2-C5 alkenyl group, and contain at least one unsaturated bond, 0≤y≤1, 0≤z≤1.
[0013] In one embodiment of the present application, the carbonate compound is selected from at least one of the following compounds: .
[0014] In one embodiment of the present application, the compound represented by formula II is selected from at least one of the following compounds: .
[0015] In one embodiment of the present application, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium perchlorate, lithium difluorophosphate and lithium difluorobis(oxalatophosphate); based on the mass of the gel electrolyte, the mass percentage of the lithium salt is 6% to 15%.
[0016] In one embodiment of the present application, the organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate and propylene carbonate.
[0017] The second aspect of the present application provides a lithium-ion battery, which includes a positive electrode plate, a negative electrode plate, a separator and the gel electrolyte described in the first aspect of the present application.
[0018] The third aspect of the present application provides a method for preparing the lithium ion battery according to the second aspect of the present application, comprising:
[0019] A precursor solution comprising the polymerization monomer, the cross-linking agent, the lithium salt, the organic solvent and the initiator is prepared; the precursor solution is injected into the shell of the lithium ion battery, and after packaging, it is allowed to stand at room temperature for 4 to 8 hours, and a thermal polymerization reaction is carried out at 30 to 80° C. for 3 to 36 hours to obtain the lithium ion battery.
[0020] In one embodiment of the present application, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; based on the mass of the gel electrolyte, the mass percentage W of the initiator is 0.01% to 0.05%.
[0021] Beneficial effects of this application:
[0022] The present application provides a gel electrolyte, a lithium ion battery and a preparation method thereof. The gel electrolyte includes a gel polymer, a lithium salt and an organic solvent; the gel polymer includes monomer units from a polymerized monomer and a crosslinking agent, the polymerized monomer is selected from a carbonate compound, and the crosslinking agent is selected from at least one of the compounds shown in Formula II. The crosslinking agent of the present application has more than two C=Cs, and can be polymerized and linked with the polymerized monomer of the present application to form a polymer network with a multidimensional and porous structure; at the same time, the strong polar carbonate group in the polymerized monomer of the present application is combined with the COC structure in the crosslinking agent to form a Li + Providing more and shorter transmission paths, thereby improving the ionic conductivity of the gel electrolyte, and enhancing the cycle performance and rate performance of the lithium-ion battery. Furthermore, the lithium-ion battery prepared by the preparation method of the present application has higher cycle performance and rate performance.
[0023] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0025] The present application provides a gel electrolyte, which includes a gel polymer, a lithium salt and an organic solvent; the gel polymer includes monomer units from a polymerized monomer and a cross-linking agent, the polymerized monomer is selected from a carbonate compound, the carbonate compound is selected from at least one of a cyclic carbonate and a linear carbonate; the cyclic carbonate is selected from at least one of the compounds shown in Formula Ia; the linear carbonate is selected from at least one of the compounds shown in Formula Ib;
[0026] Among them, A is selected from , B is selected from C2-C8 alkenyl; R1 and R2 are each independently selected from C1-C4 alkyl or C2-C5 alkenyl, and contain at least one unsaturated bond, 1≤x≤2;
[0027] The cross-linking agent is selected from at least one of the compounds shown in Formula II;
[0028] Wherein, R3 to R6 are each independently selected from C1-C4 alkyl or , and contains at least two , 0≤n≤3;
[0029] Based on the mass of the gel electrolyte, the mass percentage w of the gel polymer is 1% to 20%, preferably 1.5% to 10%. For example, the mass percentage of the gel polymer can be 1%, 5%, 10%, 15%, 20%, or a range consisting of any two of these values;
[0030] The mass ratio m1 / m2 of the polymerized monomer to the crosslinking agent is 0.1 to 4, preferably 0.5 to 2. For example, the mass ratio m1 / m2 of the polymerized monomer to the crosslinking agent can be 0.1, 0.5, 1, 2, 3, 4, or a range consisting of any two of these values.
[0031] The polymerizable monomer of the present application can be polymerized by heat initiation of its double bond structure, and the polymerization as a single polymerized unit will form a linear polymer segment with a high density of carbonate group structure. Since the carbonate group has a strong polarity, it can be Li + The transmission of Li+ provides more polar sites, but its monomer homopolymer is a linear polymer chain segment, which cannot wrap a large amount of electrolyte to swell and form a stable quasi-solid gel electrolyte. This requires the introduction of copolymerization and cross-linking into the polymer network. In the study, it was found that the cross-linking agent of the present application has more than two C=C, which can be polymerized and linked with the polymer monomer of the present application to form a multi-dimensional, porous polymer network, and the strong polar carbonate group in the polymer monomer of the present application is combined with the COC structure of the cross-linking agent, which can provide Li+ for the transmission of Li+. +Providing more and shorter transmission paths, thereby improving the ionic conductivity of the gel electrolyte and enhancing the cycle performance and rate performance of lithium-ion batteries. In addition, since the polymerized monomers of the present application are often used as friendly film-forming additives, there is no need to consider the problem of monomer residues endangering battery materials and damaging the electrochemical performance of the battery. Moreover, the polymerized monomers can preferentially form a film on the electrode surface to form a solid electrolyte interface film (SEI film) having Li2CO3, alkyl lithium carbonate, lithium divinyl dicarbonate (LDVD) and oligomers, protecting the integrity of the electrode surface, inhibiting the further occurrence of side reactions, and enhancing the cycle performance and rate performance of lithium-ion batteries.
[0032] The study found that limiting the mass percentage of the gel polymer and the mass ratio of the polymerized monomer to the cross-linking agent within the scope of this application is conducive to forming a gel polymer with a three-dimensional network structure, improving the mechanical strength and ionic conductivity of the gel electrolyte, and enhancing the cycle performance and rate performance of lithium-ion batteries. At the same time, it reduces the cost of the gel electrolyte and solves the safety problems caused by leakage of traditional liquid electrolytes.
[0033] In one embodiment of the present application, B is selected from or ; R7 and R8 are each independently selected from a hydrogen atom, a C1-C4 alkyl group or a C2-C5 alkenyl group, and contain at least one unsaturated bond, 0≤y≤1, 0≤z≤1.
[0034] In one embodiment of the present application, the carbonate compound is selected from at least one of the following compounds: .
[0035] In one embodiment of the present application, the compound represented by formula II is selected from at least one of the following compounds: .
[0036] In one embodiment of the present application, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalate borate, lithium dioxalate borate, lithium perchlorate, lithium difluorophosphate and lithium difluorobis(oxalate)phosphate; based on the mass of the gel electrolyte, the mass percentage of the lithium salt is 6% to 15%. For example, based on the mass of the gel electrolyte, the mass percentage of the lithium salt can be 6%, 8%, 10%, 12%, 15% or a range consisting of any two of the values. Selecting the above lithium salts and regulating the mass percentage of the lithium salts within the scope of the present application can make the gel electrolyte have higher ionic conductivity and good electrochemical stability, which can further improve the cycle performance and rate performance of the lithium ion battery.
[0037] In one embodiment of the present application, the organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate and propylene carbonate. The above organic solvents can make the gel electrolyte have higher ionic conductivity and good electrochemical stability, and can further improve the cycle performance and rate performance of the lithium ion battery.
[0038] In one embodiment of the present application, based on the mass of the gel electrolyte, the mass percentage of the organic solvent is 65% to 93%. For example, based on the mass of the gel electrolyte, the mass percentage of the organic solvent can be 65%, 70%, 75%, 80%, 85%, 90%, 93%, or a range consisting of any two of these values. By regulating the mass percentage of the organic solvent within the scope of the present application, the gel electrolyte can have higher ionic conductivity and good electrochemical stability, which can further improve the cycle performance and rate performance of the lithium-ion battery.
[0039] The second aspect of the present application provides a lithium-ion battery, which includes a positive electrode plate, a negative electrode plate, a separator and the gel electrolyte described in the first aspect of the present application.
[0040] In one embodiment of the present application, the positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium iron phosphate material, lithium manganese iron phosphate material, nickel cobalt manganese oxide material, lithium cobalt oxide material, lithium nickel manganese oxide material and lithium manganese-rich material; and / or, the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material is selected from at least one of silicon-based material and carbon-based material.
[0041] In the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode current collector, or it can be a partial area of the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0042] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector can be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil, aluminum alloy foil, nickel foil or nickel alloy can be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).
[0043] The present application has no particular limitation on the thickness of the positive electrode material layer and the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided positive electrode material layer is 120 μm to 150 μm, and the thickness of the positive electrode current collector is 12 μm to 19 μm.
[0044] The positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon black (SuperP), acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The binder may include but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The present application does not particularly limit the mass ratio of the positive active material, conductive agent and binder in the positive electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0045] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.
[0046] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved, for example, the positive electrode active material, the conductive agent, and the binder are mixed in a certain proportion, N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on one surface of the positive electrode collector, and after drying, a positive electrode sheet coated with a positive electrode material layer on one side is obtained. Then the above coating steps are repeated on the other surface of the positive electrode collector, and after drying, a positive electrode sheet coated with a positive electrode material layer on both sides is obtained, which is then rolled, trimmed, cut, and striped. After stripping, it is dried, and the pole ears are welded to obtain a positive electrode sheet.
[0047] In the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.
[0048] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam or copper foam may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0049] The present application has no particular limitation on the thickness of the negative electrode material layer and the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 69 μm to 80 μm, and the thickness of the negative electrode current collector is 6 μm to 12 μm.
[0050] In one embodiment of the present application, the negative electrode material layer may further include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon black (Super P), acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fibers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The binder may include but is not limited to at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode material layer. Those skilled in the art may select according to actual needs as long as the purpose of the present application can be achieved.
[0051] In one embodiment of the present application, the negative electrode material layer may further include a conductive agent, a binder and a thickener. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the above conductive agent and the above binder. The thickener may include but is not limited to at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0052] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it may be at least one of the above conductive agent and the above binder.
[0053] The present application has no particular restrictions on the preparation method of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode active material, thickener, binder and conductive agent can be mixed in a certain mass ratio, deionized water can be added and stirred evenly to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on one surface of the negative electrode current collector, and after drying, a negative electrode sheet coated with a negative electrode material layer on one side is obtained. Then, the above coating steps are repeated on the other surface of the negative electrode current collector, and after drying, a negative electrode sheet coated with a negative electrode material layer on both sides is obtained, which is then rolled, trimmed, cut, and striped. After stripping, it is dried, and the pole ears are welded to obtain a negative electrode sheet.
[0054] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm can be selected from but not limited to at least one of polyethylene (PE), polypropylene (PP), glass fiber, polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI) and polyamide (PA). The type of diaphragm may include at least one of a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane and a spun membrane. In the present application, the thickness of the diaphragm is not particularly limited, as long as the purpose of the present application can be achieved, for example, the thickness of the diaphragm may be 8 μm to 18 μm.
[0055] In the present application, the lithium-ion battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and a gel electrolyte, as well as other components known in the field of lithium-ion batteries, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, and it can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, the shell can be a hard shell shell or a flexible shell. The material of the hard shell shell can be metal, and the present application does not limit the type of metal, and a metal hard shell shell known in the art can be used, as long as the purpose of the present application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0056] The preparation process of the lithium-ion battery of the present application is well known to those skilled in the art and is not particularly limited in the present application. For example, the preparation process of the lithium-ion battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting a gel electrolyte precursor solution into the shell and sealing it, standing it, performing a thermal polymerization treatment, and then performing formation, exhaust and other processes to obtain a lithium-ion battery.
[0057] The third aspect of the present application provides a method for preparing a lithium ion battery according to the second aspect of the present application, comprising: preparing a precursor solution comprising the polymerizable monomer, the crosslinking agent, the lithium salt, the organic solvent and the initiator; injecting the precursor solution into the shell of the lithium ion battery, and after packaging, standing at room temperature for 4 to 8 hours, and performing a thermal polymerization reaction at 30 to 80°C for 3 to 36 hours to obtain the lithium ion battery. For example, the standing time at room temperature can be 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, the temperature of the thermal polymerization reaction can be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or a range consisting of any two of the numerical values, and the time of the thermal polymerization reaction can be 3 hours, 12 hours, 24 hours, 36 hours or a range consisting of any two of the numerical values. The preparation of the lithium ion battery is carried out under the above conditions, which is conducive to the in-situ polymerization reaction of the precursor solution in the lithium ion battery to form a stable and solidified gel electrolyte. In the present application, room temperature refers to 20 to 30°C.
[0058] In one embodiment of the present application, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; based on the mass of the gel electrolyte, the mass percentage W of the initiator is 0.01% to 0.05%. For example, based on the mass of the gel electrolyte, the mass percentage of the initiator can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05% or a range consisting of any two of the values. Selecting the above initiators and regulating the mass percentage of the initiators within the scope of the present application is beneficial to controlling the speed of the polymerization reaction and the cross-linking density of the polymer, and is beneficial to controlling the molecular weight of the polymer, avoiding problems such as implosion or increased viscosity causing a decrease in conductivity.
[0059] Example
[0060] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0061] Test methods and equipment:
[0062] Conductivity test
[0063] Using a DDS-307 conductivity meter (Shanghai Leici Instrument Co., Ltd.), the electrode probe and the gel electrolyte precursor solution were sealed in a container, placed in an oil bath and heated at 60°C for curing. After a stable gel was obtained, the conductivity of the gel was tested and its conductivity value was recorded as σ.
[0064] 25℃ Cyclic Performance Test
[0065] Place the lithium-ion battery in a 25℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.2V at a constant current of 1C, then charge it at a constant voltage of 4.2V until the cut-off current is 0.05C, and discharge it to 2.75V at a constant current of 1C. Record the initial discharge capacity as C0. This is a charge and discharge cycle. Repeat the above charge and discharge cycles until the capacity decays to 80% C0, and record the number of cycles N. The greater the number of cycles, the better the cycle performance of the lithium-ion battery.
[0066] 45℃ Cyclic Performance Test
[0067] Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.2V at a constant current of 1C, then charge it at a constant voltage of 4.2V until the cut-off current is 0.05C, and discharge it to 2.75V at a constant current of 1C. Record the initial discharge capacity as Q0. This is a charge and discharge cycle. Repeat the above charge and discharge cycles until the capacity decays to 80% Q0, and record the number of cycles M. The greater the number of cycles, the better the cycle performance of the lithium-ion battery.
[0068] 25℃ rate performance test
[0069] Place the lithium-ion battery in a 25°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge to 4.2V at 0.5C constant current, then charge at 4.2V at constant voltage to a cut-off current of 0.05C, discharge to 2.75V at 0.5C constant current, repeat the above charge and discharge steps 10 times, and record the 10th discharge capacity as D1; charge to 4.2V at 1.0C constant current, charge to 4.2V at constant voltage to a cut-off current of 0.05C, and then discharge to 2.75V at 1.0C constant current, repeat the above charge and discharge cycle 10 times, and record the 10th discharge capacity as D2; charge to 4.2V at 1.5C constant current, charge to 4.2V at constant voltage to a cut-off current of 0.05C, and then discharge to 2.75V at 1.5C constant current, repeat the above charge and discharge cycle 10 times, and record the 10th discharge capacity as D3; charge to 4.2V at 2.0C constant current, charge to 4.2V at constant voltage to a cut-off current of 0.05C, and then discharge to 2.75V at 2.0C constant current. C constant current discharge to 2.75V, repeat the above charge and discharge cycle 10 times, and record the 10th discharge capacity as D4.
[0070] Capacity retention rate (%) = D4 / D1×100%; the greater the capacity retention rate, the better the rate performance of the lithium-ion battery.
[0071] Example 1
[0072] <Preparation of Gel Electrolyte Precursor Solution>
[0073] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of 3:7 to obtain a base solvent; then lithium salt lithium hexafluorophosphate (LiPF6) was added, dissolved and mixed to obtain an electrolyte;
[0074] The polymerizable monomer (Formula I-1) is mixed with a cross-linking agent, pentaerythritol tetraacrylate (PETA, Formula II-10), and an initiator, azobisisobutyronitrile (AIBN), and the mixture is uniformly mixed to obtain a polymer precursor solution;
[0075] The polymer precursor solution and the electrolyte are mixed together to obtain a gel electrolyte precursor solution; wherein, based on the mass of the gel electrolyte precursor solution, the mass percentage of the lithium salt is 12.5%, the mass percentage of the basic solvent is 85%, the mass percentage of the polymerized monomer is 1.25%, the mass percentage of the cross-linking agent is 1.25%, and the mass percentage of the initiator is 0.022%.
[0076] <Preparation of positive electrode sheet>
[0077] The positive electrode active material is lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive agent superconducting carbon black (Super P) and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 92.5:5:2.5, N-methylpyrrolidone (NMP) is added to prepare a slurry with a solid content of 60wt%, and the positive electrode slurry is obtained after vacuum stirring; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 16 μm, and dried at 80°C to obtain a positive electrode sheet with a single-sided positive electrode material layer; then the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer; then it is rolled, trimmed, cut and slit, and after slitting, it is dried at 85°C for 4 hours under vacuum conditions, and the pole ears are welded to obtain a positive electrode sheet with a specification of 540 mm×50 mm for standby use; wherein the thickness of the single-sided positive electrode material layer is 125 μm.
[0078] <Preparation of negative electrode sheet>
[0079] The negative electrode active material silicon carbide material (model: SiC550, manufacturer: Liyang Tianmu Pioneer Battery Material Technology Co., Ltd.), conductive agent superconducting carbon black (Super P), single-walled carbon nanotubes (SWCNT), thickener sodium carboxymethyl cellulose (CMC-Na) and adhesive styrene butadiene rubber (SBR) were mixed according to a mass ratio of 87.94:6:0.06:2:4, and deionized water was added as a solvent to prepare a slurry with a solid content of 49 wt%, and the negative electrode slurry was obtained after vacuum stirring. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 9 μm, and dried at 85°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side; then the above steps were repeated on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides; then the sheet was rolled, trimmed, cut and slit, and then dried at 85°C for 4 hours under vacuum conditions, and the tabs were welded to obtain a sheet with a specification of 660 mm×59 mm negative electrode sheet; wherein the thickness of the single-sided negative electrode material layer is 73 μm.
[0080] <Preparation of Separator>
[0081] Polyethylene with a thickness of 12 µm (provided by Shenzhen Xingyuan Material Technology Co., Ltd.) was used as the separator.
[0082] <Preparation of lithium-ion batteries>
[0083] The prepared positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound, the positive electrode ear is connected to the positive electrode sheet, and the negative electrode ear is connected to the negative electrode sheet to obtain an electrode assembly. The electrode assembly is placed in an aluminum plastic film packaging bag, and vacuum baked at 85°C for 48 hours, and the prepared gel electrolyte precursor solution is injected, and the injection coefficient is 3 g / Ah. After vacuum packaging, it is left to stand at room temperature for 12 hours to allow the electrode sheet, separator and gel electrolyte precursor solution to be fully infiltrated; then a polymer fixture forming machine (model: NP-5AFF, manufacturer: Shenzhen Xinpu Automation Equipment Co., Ltd.) is used to place it at a temperature of 60°C for thermal polymerization for 12 hours, and then the forming, exhaust and other processes are carried out to obtain a formed lithium-ion battery; wherein, the forming current is 0.1C, the forming upper limit voltage is 4.2V, and the forming temperature is 25°C.
[0084] Example 2 to Example 22
[0085] Except that the type of polymerizable monomers was changed according to Table 1 in the preparation of gel electrolyte precursor solution, the rest was the same as that of Example 1.
[0086] Example 23 to Example 33
[0087] Except that the type of the cross-linking agent was changed according to Table 1 in the preparation of the gel electrolyte precursor solution, the rest was the same as that of Example 14.
[0088] Example 34 to Example 37
[0089] The process is the same as Example 14 except that in the preparation of gel electrolyte precursor solution, the mass percentage of the gel polymer (polymerized monomer and cross-linking agent) is changed according to Table 1, and the mass percentage of the base solvent is changed accordingly.
[0090] Example 38 to Example 41
[0091] Except that the mass ratio of the polymerizable monomer and the cross-linking agent is changed according to Table 1 in the preparation of the gel electrolyte precursor solution, the rest is the same as that of Example 14.
[0092] Comparative Example 1 to Comparative Example 2
[0093] The process is the same as Example 14 except that in the preparation of gel electrolyte precursor solution, the mass percentage of the gel polymer (polymerized monomer and cross-linking agent) is changed according to Table 1, and the mass percentage of the base solvent is changed accordingly.
[0094] Comparative Example 3 to Comparative Example 4
[0095] Except that the mass ratio of the polymerizable monomer and the cross-linking agent is changed according to Table 1 in the preparation of the gel electrolyte precursor solution, the rest is the same as that of Example 14.
[0096] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.
[0097] Table 1
[0098] From Example 1 to Example 41, Comparative Examples 1 to Comparative Examples 4, it can be seen that if the content of the gel polymer is not within the scope of the present application, or the mass ratio of the polymerized monomer to the cross-linking agent is not within the scope of the present application, the high ionic conductivity of the gel electrolyte and the high cycle performance and high rate performance of the lithium ion battery cannot be simultaneously met, resulting in poor overall effect of the lithium ion battery; by selecting the polymerized monomer and the cross-linking agent of the present application, and limiting the content of the gel polymer and the mass ratio of the polymerized monomer to the cross-linking agent within the scope of the present application, the high ionic conductivity of the gel electrolyte and the high cycle performance and high rate performance of the lithium ion battery can be simultaneously met, resulting in the best overall effect of the lithium ion battery. The above results illustrate that the gel electrolyte of the present application has high ionic conductivity, and the lithium ion battery of the present application has high cycle performance and rate performance.
[0099] The type of polymerized monomer usually affects the ionic conductivity of the gel electrolyte and the cycle performance and rate performance of the lithium ion battery. It can be seen from Examples 1 to 22 that the gel polymer includes monomer units from polymerized monomers within the scope of the present application, which can simultaneously meet the high ionic conductivity of the gel electrolyte and the high cycle performance and high rate performance of the lithium ion battery.
[0100] The type of cross-linking agent usually affects the ionic conductivity of the gel electrolyte and the cycle performance and rate performance of the lithium-ion battery. It can be seen from Examples 23 to 33 that the gel polymer includes monomer units from the cross-linking agent within the scope of the present application, which can simultaneously meet the high ionic conductivity of the gel electrolyte and the high cycle performance and high rate performance of the lithium-ion battery.
[0101] The content of the gel polymer usually affects the ionic conductivity of the gel electrolyte and the cycle performance and rate performance of the lithium ion battery. It can be seen from Example 14 and Example 34 to Example 37 that limiting the content of the gel polymer to within the scope of the present application can simultaneously meet the high ionic conductivity of the gel electrolyte and the high cycle performance and high rate performance of the lithium ion battery.
[0102] The mass ratio of the polymerized monomer to the cross-linking agent usually affects the ionic conductivity of the gel electrolyte and the cycle performance and rate performance of the lithium-ion battery. It can be seen from Examples 14 and 38 to 41 that the mass ratio of the polymerized monomer to the cross-linking agent is within the scope of the present application, which can better meet the high ionic conductivity of the gel electrolyte and the high cycle performance and high rate performance of the lithium-ion battery.
[0103] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A gel electrolyte, characterized in that: The invention comprises a gel polymer, a lithium salt and an organic solvent; the gel polymer comprises monomer units from a polymerized monomer and a cross-linking agent, the polymerized monomer is selected from a carbonate compound, the carbonate compound is selected from at least one of a cyclic carbonate and a linear carbonate; the cyclic carbonate is selected from at least one of the compounds shown in formula Ia; the linear carbonate is selected from at least one of the compounds shown in formula Ib; ; Among them, A is selected from , B is selected from C2-C8 alkenyl; R1 and R2 are each independently selected from C1-C4 alkyl or C2-C5 alkenyl, and contain at least one unsaturated bond, 1≤x≤2; The cross-linking agent is selected from at least one of the compounds shown in Formula II; ; Wherein, R3 to R6 are each independently selected from C1-C4 alkyl or , and contains at least two , 0≤n≤3; Based on the mass of the gel electrolyte, the mass percentage w of the gel polymer is 1% to 20%; The mass ratio m1 / m2 of the polymerizable monomer to the cross-linking agent is 0.1-4.
2. The gel electrolyte according to claim 1, characterized in that w is 1.5%~10%, m1 / m2 is 0.5~2.
3. The gel electrolyte according to claim 1, characterized in that B is selected from or ; R7 and R8 are each independently selected from a hydrogen atom, a C1-C4 alkyl group or a C2-C5 alkenyl group, and contain at least one unsaturated bond, 0≤y≤1, 0≤z≤1.
4. The gel electrolyte according to claim 1, characterized in that The carbonate compound is selected from at least one of the following compounds: 。 5. The gel electrolyte according to claim 1, characterized in that: The compound represented by formula II is selected from at least one of the following compounds: 。 6. The gel electrolyte according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium perchlorate, lithium difluorophosphate and lithium difluorobis(oxalatophosphate); based on the mass of the gel electrolyte, the mass percentage of the lithium salt is 6% to 15%.
7. The gel electrolyte according to claim 1, characterized in that The organic solvent is selected from at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate and propylene carbonate.
8. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the gel electrolyte according to any one of claims 1 to 7.
9. A method for preparing a lithium ion battery according to claim 8, characterized in that: include: preparing a precursor solution comprising the polymerization monomer, the cross-linking agent, the lithium salt, the organic solvent and an initiator; The precursor solution is injected into the shell of the lithium ion battery, and after packaging, it is left to stand at room temperature for 4 to 8 hours, and a thermal polymerization reaction is carried out at 30 to 80° C. for 3 to 36 hours to obtain the lithium ion battery.
10. The preparation method according to claim 9, characterized in that: The initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; based on the mass of the gel electrolyte, the mass percentage W of the initiator is 0.01% to 0.05%.
Citation Information
Patent Citations
Multi-application-field high-rate gel electrolyte and preparation method thereof
CN116864796A
Gel electrolyte precursor and application thereof
US20230352731A1